Education Through Labor: From the deuxième portion du contingent to the Youth Civic Service in West Africa (Senegal/Mali, 1920s-1960s) - (:unkn) unknown (My University, 2020)
Under the French colonial regime, the “second portion” of the military was used as labour brigades, compelled to serve for two years in works of public nature. They were encamped in labor camp and were taught the value of work as well as discipline and basic rules of hygiene. After the independence of the francophone West African countries in 1960, postcolonial leaders in Senegal and Mali try to implement a civil service for the youth in order to offer them basic education. In reality, the civil service appears as a way to control and use the recruits for economic purposes echoing in some extent the former colonial “second portion du contingent.” More broadly, through the analysis of the legacies and continuities, I argue that the postcolonial elites perpetuate the “civilizing mission,” no more for the so-called mise en valeur of the colonies but for the development of the territory.
Keywords: African Research